Design thinking: Opinions and experiences of middle school students - Ciftci, Ayse; Topcu, Mustafa Sami (PEGEM AKAD YAYINCILIK EGITIM DANISMANLIK HIZMETLERI TIC LTD STI, 2020)
The aim of the present research is to examine the opinions and experiences of 7th grade students towards design thinking. In this context, activities for design thinking about energy transformations included in the science curriculum were conducted for four weeks. Phenomenology method, one of the qualitative research methods, was used in the study carried out with thirty-six 7th grade students. The students' opinions about design thinking were obtained through open-ended questions and their experiences through diaries. Content analysis method was used to analyse the data collected from the open-ended questionnaire and the student diaries. In line with the students' views on design thinking, 7 themes emerged: Contributions of design thinking, difficulties encountered in the implementation of design thinking, difficulty level of design thinking stages, getting support during the implementation of design thinking, degree of appreciation of design thinking stages, spending time for design thinking activities in the future and participating in design thinking activities outside of school. As a result of the analysis of the diaries, three themes emerged: learning, satisfaction and criticism. It is thought that the opinions and experiences of middle school students towards design thinking will contribute to the design of learning environments in a more qualified way.
Keywords: Design thinking; Middle school students; Opinion; Experience; TEACHERS EXPERIENCES; Education & Educational Research